Tasawuf in Sharia Obstacles: The Dynamics of The Persecution of The Naqsabandiyah Tarekat Prof.Dr.H.Kadirun Yahya in Langsa, Aceh - Mulizar; Syafieh (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
This article discusses about the dynamics of persecution in Langsa which carried out by the government against the Naqsabandiyah tarekat, the foundation of Prof. Dr. Kadirun Yahya. The purpose of this study is to observe the dynamics of persecution toward the Thariqat Naqsabandiyah Khalidiyah, the foundation of Prof. Dr. Kadirun Yahya in Seulalah Baru of Langsa City in the province of Aceh since the thariqat is considered to deviate by some citizens. The type of this research is qualitative with socio-anthropological and ethnographic approaches. The writer collected the data through literature and field studies. This study found that there was an effort of the persecution to close the Naqsabandiyah Thariqat temporaryly by the government of Langsa because the tarekat was considered as heretic in society. In that case, the one who acted was the Islamic Sharia Department of Langsa. Actually, the tarekat is such a good thing, and it is also a platform and wasilah in getting closer to the creator. Moreover, there are problems in society and the local government such one of them is the dynamics of the persecution against the tarekat Naqsabandiyah, Foundation of Prof. Dr. H. Kadirun Yahya in Langsa. Abstract: Artikel ini membahas dinamika persekusi yang dilakukan pemerintah terhadap kelompok tarekat naqsabandiyyah yayasan Prof.Dr.Kadirun Yahya yang terjadi di kota langsa. Tujuan dari penelitian ini adalah ingin mengetahui dinamika persekusi Thariqat Naqsabandiyah Khalidiyah Yayasan Prof. Dr. H. Kadirun Yahya di Seulalah Baru Langsa, Aceh yang dianggap sesat oleh sebagian masyarakat. Jenis penelitian ini adalah kualitatif dengan pendekatan sosio-antropologi dan etnografi. Penulis mengumpulkan data melalui studi pustaka dan lapangan. Adapun temuan dari penelitian ini adalah persekusi yang dilakukan terhadap tarekat naqsabandiyyah berupa adanya usaha penutupan sementara dari pihak pemerintah kota langsa, dalam hal ini yang bertindak adalah dinas syariat Islam kota Langsa, dikarenakan di anggap sesat tarekat tersebut di masyarakat. Ternyata tarekat yang selama ini dianggap di masyarakat sesuatu hal yang baik, dan merupakan wadah serta wasilah dalam mendekatkan diri pada sang pencipta, terdapat problematika di masyarakat dan pada pemerintah setempat, salah satu dinamika yang terjadi yaitu persekusi yang dilakukan terhadap tarekat Naqsabandiyyah yayasan Prof.Dr.H.Kadirun Yahya di Langsa